2009
DOI: 10.1590/s1414-32832009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Concepções de docentes e discentes acerca de metodologias de ensino-aprendizagem: análise do caso do Curso de Enfermagem da Universidade Estadual Vale do Acaraú em Sobral - Ceará

Abstract: Este estudo buscou conhecer a concepção de docentes e discentes do Curso de Enfermagem da Universidade Estadual Vale do Acaraú acerca de metodologias de ensino-aprendizagem. A coleta de dados deu-se por meio de grupos focais com estudantes e professores e observação participante em sala de aula, entre junho e julho de 2006. A análise foi orientada pelo referencial da hermenêutica-dialética. Os discursos revelaram que manifestações de poder permeiam a relação pedagógica. A análise de divergências e convergência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
1
3
0
6
Order By: Relevance
“…12,17 It is also revealed that it is still necessary to go a long way so that the HEI can advance towards the determinations of the NCDs; Thus, the teaching-learning process in health occurs centered on the teacher as the sole holder of the knowledge, which transmits it to the student, who receives it passively. 15,35 It is evaluated that this fact corroborates the studies that demonstrate the necessity that the university institutions demand to reach the requirements of the NCD's. It is pointed out that, in order to apply the AMs, it is fundamental that the institutions adjust to the new teaching-learning model that requires changes in infrastructure, new equipment and teacher development programs, aimed at pedagogical training and an integrated curriculum, since the disarticulation of the curriculum generates the greatest difficulty of the teaching activity, according to the progressive vision.…”
Section:  Opinions Of Health Professionals On Active Methodologiessupporting
confidence: 60%
See 1 more Smart Citation
“…12,17 It is also revealed that it is still necessary to go a long way so that the HEI can advance towards the determinations of the NCDs; Thus, the teaching-learning process in health occurs centered on the teacher as the sole holder of the knowledge, which transmits it to the student, who receives it passively. 15,35 It is evaluated that this fact corroborates the studies that demonstrate the necessity that the university institutions demand to reach the requirements of the NCD's. It is pointed out that, in order to apply the AMs, it is fundamental that the institutions adjust to the new teaching-learning model that requires changes in infrastructure, new equipment and teacher development programs, aimed at pedagogical training and an integrated curriculum, since the disarticulation of the curriculum generates the greatest difficulty of the teaching activity, according to the progressive vision.…”
Section:  Opinions Of Health Professionals On Active Methodologiessupporting
confidence: 60%
“…And "how to do it?". 15,27, It is noteworthy that, of the international articles, only one highlighted teachers with good knowledge and attitudes favorable to PBL. 28 It is therefore necessary for teachers to devote themselves intensely to their pedagogical preparation, in order to understand the characteristics of the AMs to face the challenges that lead to the preparation of analytical students; In this way, the role of the teacher must change from "knowledge provider" to "learning creator", leaving the comfort zone of traditionalism and offering more effort to master and implement innovative pedagogical practices that stimulate the student in learning to learn.…”
Section:  Knowledge Of Teachers In the Health Area On Active Methodologiesmentioning
confidence: 99%
“…O processo de mudança de concepções é complexo e exige dos profissionais envolvidos interesse, paciência e perseverança, pois são as pessoas que devem ter as práticas ressignificadas. Portanto, um novo modelo de ensino pressupõe uma nova "cultura" pedagógica a ser incorporada pelas pessoas que constituem a instituição (TEÓFILO;DIAS, 2009). A gestão do serviço das unidades de saúde que recebem alunos deve estreitar as relações com os gestores da universidade que demanda esses alunos e com preceptores e docentes.…”
Section: Gestãounclassified
“…6 In addition, it must be considered that it comes to the education of adults and therefore presuppose the use of active teaching and learning methodologies. 7 in this context, the Andragogy, art and science of driving adults to learning, directs the teaching a model that incorporates concepts of self-direction, independent study, individualized…”
mentioning
confidence: 99%